Break of symmetry at the surface of IrTe2 upon phase transition measured by x-ray photoelectron diffraction. (1st December 2021) - Rumo, Maxime; Pulkkinen, Aki; Ma, KeYuan; von Rohr, Fabian O; Muntwiler, Matthias; Monney, Claude
Abstract: IrTe2 undergoes a series of charge-ordered phase transitions below room temperature that are characterized by the formation of stripes of Ir dimers of different periodicities. Full hemispherical x-ray photoelectron diffraction (XPD) experiments have been performed to investigate the atomic position changes undergone near the surface of 1 T -IrTe2 in the first-order phase transition, from the (1 × 1) phase to the (5 × 1) phase. Comparison between experiment and simulation allows us to identify the consequence of the dimerization on the Ir atoms local environment. We report that XPD permits to unveil the break of symmetry of IrTe2 trigonal to a monoclinic unit cell and confirm the occurrence of the (5 × 1) reconstruction within the first few layers below the surface with a staircase-like stacking of dimers.